Can Complete Blood Count Inflammation Markers Be Used to Predict Graft Success After Tympanoplasty? - Zehra Çınar; Özgür Yiğit; Ahmet Volkan Sünter (İstanbul Medical Journal, 2020)

(untitled)
Introduction:This study aimed to investigate the effect of preoperative neutrophil lymphocyte ratio (NLR), platelet lymphocyte ratio (PLR), eosinophil lymphocyte ratio (ELR), basophil lymphocyte ratio (BLR) and lymphocyte monocyte ratio (LMR) on graft success after tympanoplasty.Methods:Forty-five patients who underwent tympanoplasty with temporal fascia graft between January 2017 and December 2019 were included in this study. The patients were divided into two groups: intact (13 men, 12 women) and perforated (13 women, 7 men) according to their postoperative graft results. Demographic data and routine complete blood count parameters, such as NLR, PLR, ELR, BLR and LMR, as well as intraoperative middle ear characteristics were compared for both the groups.Results:The following parameters did not differ significantly differ (p>0.05) in both groups: age; gender; side; middle ear condition; platelet, neutrophil, lymphocyte, eosinophil, monocyte and basophil counts; NLR; PLR; ELR; BLR and LMR.Conclusion:From the results, it can be concluded that NLR, PLR, ELR, BLR and LMR, which are markers of inflammation in the preoperative period, cannot be used to predict graft success in patients who will undergo tympanoplasty for chronic otitis media.